STAT3 Partly Inhibits Cell Proliferation via Direct Negative Regulation of FST Gene Expression - Xu, Haidong; Ma, Guangwei; Mu, Fang; Ning, Bolin; Li, Hui; Wang, Ning (Frontiers in Genetics, 2021)
Follistatin (FST) is a secretory glycoprotein and belongs to the TGF-β superfamily. Previously, we found that two single nucleotide polymorphisms (SNPs) of sheep FST gene were significantly associated with wool quality traits in Chinese Merino sheep (Junken type), indicating that FST is involved in the regulation of hair follicle development and hair trait formation. The transcription regulation of human and mouse FST genes has been widely investigated, and many transcription factors have been identified to regulate FST gene. However, to date, the transcriptional regulation of sheep FST is largely unknown. In the present study, genome walking was used to close the genomic gap upstream of the sheep genomic FST gene and to obtain the FST gene promoter sequence. Transcription factor binding site analysis showed sheep FST promoter region contained a conserved putative binding site for signal transducer and activator of transcription 3 (STAT3), located at nucleotides -423 to -416 relative to the first nucleotide (A, +1) of the initiation codon (ATG) of sheep FST gene. The dual-luciferase reporter assay demonstrated that STAT3 inhibited the FST promoter activity and that the mutation of the putative STAT3 binding site attenuated the inhibitory effect of STAT3 on the FST promoter activity. Additionally, chromatin immunoprecipitation assay (ChIP) exhibited that STAT3 is directly bound to the FST promoter. Cell proliferation assay displayed that FST and STAT3 played opposite roles in cell proliferation. Overexpression of sheep FST significantly promoted the proliferation of sheep fetal fibroblasts (SFFs) and human keratinocyte (HaCaT) cells, and overexpression of sheep STAT3 displayed opposite results, which was accompanied by a significantly reduced expression of the FST gene (P < 0.05). Taken together, STAT3 directly negatively regulates the sheep FST gene and depresses cell proliferation. Our findings may contribute to understanding molecular mechanisms that underlie hair follicle development and morphogenesis.